Speed control of induction motor using DTC and Fuzzy-P controller - Barriga Turriago, Camilo; Perdomo Charry, Cesar Andrey (Visión electrónica, 2014)
Recently, it has greatly increased the use of fuzzy logic as a tool of artificial intelligence in the fields of power electronics and control systems motor speed. Therefore, this article describes research findings that support the implementation by simulation, an intelligent controller for speed control of an induction motor (IM) squirrel cage rotor using Direct Torque Control (DTC). DTC and its integration with a proportional fuzzy controller is described. The performance of the proposed control has been presented and analyzed under different scenarios on the engine: load starting with the controller and load variations; increase and sudden release of load; increased load and speed profile tracking.